Pericardial tamponade, a diagnostic chameleon: from the historical perspectives to contemporary management - Kaemmerer, Ann-Sophie; Alkhalaileh, Khaleel; Suleiman, Mathieu; Kopp, Markus; Hauer, Christine; May, Matthias; Uder, Michael; Weyand, Michael; Harig, Frank (Journal of Cardiothoracic Surgery, 2023)
Background: Pericardial tamponade (PT) early after cardiac surgery is a challenging clinical entity, not infrequently misrecognized and often only detected late in its course. Because the clinical signs of pericardial tamponade can be very unspecific, a high degree of initial suspicion is required to establish the diagnosis. In addition to clinical examination the deployment of imaging techniques is almost always mandatory in order to avoid delays in diagnosis and to initiate any necessary interventions, such as pericardiocentesis or direct cardiac surgical interventions. After a brief overview of how knowledge of PT has developed throughout history, we report on an atypical life-threatening cardiac tamponade after cardiac surgery. A 74-year-old woman was admitted for elective biological aortic valve replacement and aorto-coronary-bypass grafting (left internal mammary artery to left anterior descending artery, single vein graft to right coronary artery). On the 10th postoperative day, the patient unexpectedly deteriorated. She rapidly developed epigastric pain radiating to the left upper abdomen, and features of low peripheral perfusion and shock. There were no clear signs of pericardial tamponade either clinically or echocardiographically. Therefore, for further differential diagnosis, a contrast-enhanced computed tomography scan was performed under clinical suspicion of acute abdomen. Unexpectedly, active bleeding distally from the right coronary anastomosis was revealed. While the patient was prepared for operative revision, she needed cardiopulmonary resuscitation, which was successful. Intraoperatively, the source of bleeding was located and surgically relieved. The subsequent postoperative course was uneventful. Conclusions: In the first days after cardiac surgery, the occurrence of life-threatening situations, such as cardiac tamponade, must be expected. Especially if the symptoms are atypical, the entire diagnostic armamentarium must be applied to identify the origin of the complaints, which may be cardiac, but also non-cardiac. Central message: A high level of suspicion, immediate diagnostic confirmation, and rapid treatment are required to recognize and successfully treat such an emergency (Fig. 5). Perspective: Pericardial tamponade should always be considered as a complication of cardiac surgery, even when symptoms are atypical. The full range of diagnostic tools must be used to identify the origin of the complaints, which may be cardiac, but also non-cardiac (Fig. 5).
CRIS-Team Scopus Importer:2023-02-17
Keywords: Cardiac tamponade; Diagnostics; Historical aspects; Pericardial effusion; Postoperative complication